2019
DOI: 10.16986/huje.2019051160
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Different Reading Strategies with Eye Tracking Measures in Paragraph Questions

Abstract: Bu çalışmada farklı tür ve zorluklardaki çoktan seçmeli okuduğunu anlama sorularının çözümünde kullanılan iki farklı soru çözme stratejisinin başarı, soru çözme süresi, odaklanma sayısı ve okunulan alana tekrar geri dönme sayısı üzerindeki etkisinin araştırılması amaçlanmıştır. Tam deneysel olarak yürütülen bu çalışmada 28 katılımcı rastgele olarak iki gruba ayrılmıştır. Önce soru kökü stratejisini (Ö-SkS) kullanan grup, soruları önce soru kökünü okuyarak, önce paragraf stratejisini (Ö-PS) kullanan grup ise, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 28 publications
4
14
0
Order By: Relevance
“…Similar to Bayrak Karsli et al (2020) and Zhao et al (2020), this study failed to replicate the benefit that Cerdán et al (2009) found for TFs over QFs in performance accuracy when test time was unlimited (see Table 1). Our students in the untimed groups were equally successful in answering the questions, whether they did or did not read the Regarding search efficiency, we found an advantage for the TFs over the QFs, consistent with Bayrak Karsli et al 's (2020) and Cerdán et al 's (2009) findings.…”
Section: Text-first Versus Question-first Strategiesmentioning
confidence: 63%
See 4 more Smart Citations
“…Similar to Bayrak Karsli et al (2020) and Zhao et al (2020), this study failed to replicate the benefit that Cerdán et al (2009) found for TFs over QFs in performance accuracy when test time was unlimited (see Table 1). Our students in the untimed groups were equally successful in answering the questions, whether they did or did not read the Regarding search efficiency, we found an advantage for the TFs over the QFs, consistent with Bayrak Karsli et al 's (2020) and Cerdán et al 's (2009) findings.…”
Section: Text-first Versus Question-first Strategiesmentioning
confidence: 63%
“…Two other studies, which used shorter texts and closed-ended questions, did not find a clear benefit for TFs over QFs (Bayrak Karsli et al, 2020;Zhao et al, 2020). Bayrak Karsli et al (2020) asked two groups of university students to read on a computer screen short passages and answer one multiple-choice question presented below each passage, while their eye movements were monitored.…”
Section: Empirical Findingsmentioning
confidence: 99%
See 3 more Smart Citations